High-quality cardiac surgery through teamwork. Issue 1 (2nd January 2021) - Hamman, Baron L.; Henry, A. Carl; Hebeler, Robert F.; Rafael, Aldo E.; Gonzalez-Stawinski, Gonzalo V.; Enter, Daniel H.; Mercado-Reza, Aaron; Leeper, Bobbi; Roberts, Charles S.
Abstract: The high-quality cardiothoracic surgery program is primed for mindful effective surgery. The challenge lies in attaining mindful skills and efficiency. Herein is one journey toward high departmental quality over two decades.